The Effect of Parenting Styles for Childrens Behaviour on Using Gadget at Revolution Industry - Avanti Vera Risti Pramudyani (LPPM Universitas Pahlawan Tuanku Tambusai, 2021)
This study aims to know of understanding of authoritative parenting style and affected the children behaviour while using a gadget. This is qualitative with data collection from an interview, observation, and document. Analysis of the data used by Miles and Huberman. The subject is parents and their children lived at Yogyakarta. This result is the parents with authoritative parenting can classify, analyze, comparing, and evaluate their parenting style. With those understanding gives the effect on children when the children used gadget at home such as show discipline and follow the parent's rules; the children have critical thinking and independent using the gadget. Even though authoritative parenting identical with gives freedom, they have to give limit time for children to use a gadget, 6 - 7 hours in a week. Another recommendation does not give the children a gadget even though a gadget is one of the basic need for communication.